Maintenance of virologic suppression in individuals on antiretroviral therapy after switching to dual therapy: a cohort study (Research, Society and Development, 2022)
Objective: To evaluate the effectiveness of dual therapy in individuals who underwent exchange, by maintaining a viral load < 50 copies/ml and in cases of exchange due to impaired renal function. If there was a change in creatinine clearance, serum creatinine and serum phosphorus. Methods: Retrospective cohort of individuals > 18 years, who switched to dual therapy, followed up for up to 116 weeks and outcomes were evaluated up to 48 and/or up to 96 weeks after switching. Data were collected from July 2020 to June 2021, through clinical records and consultation with the Laboratory Examination Control System (Siscel) and the Medication Logistic Control System (Siclom). Analyzes were performed using SPSS software. Results: Most individuals were male (65.5%), the mean age at exchange was 54.4 years. The most used dual therapy regimen was the association of DTG+3TC (73.6%). The main reason for switching was impaired renal function (40%), the most discontinued drug was TDF (55.79%). Most subjects maintained viral suppression for up to 48 weeks after switching (n=84, 96.8%). Two individuals (2.3%) did not achieve CV suppression in this period, with values of 51 and 55 copies/ml of virus. There was no significant change in GFR comparing baseline levels with those at 48 weeks post-switch. As for phosphorus, comparing the baseline value with the value measured 48-96 weeks post-exchange, there was a slight increase, with statistical significance (2.70 ± 0.76 mg/dl vs. 3.14 ± 0.47; p=0.026). Conclusion: Most subjects maintained viral suppression at 48 and 96 weeks, demonstrating the effectiveness of dual therapy. Among those who switched due to impaired renal function, there was no improvement in glomerular filtration rate at 48 weeks, but an increase in phosphorus excretion was observed, which requires further studies, with a larger sample and longer follow-up.